2007
DOI: 10.1007/s11627-007-9084-z
|View full text |Cite
|
Sign up to set email alerts
|

Thidiazuron-induced hypertrophic growth from foliar disks of Kalanchoe pinnata leads to visualization of a bioactive auxin gradient across the leaf plane

Abstract: Thidiazuron induces a variety of effects in foliar explants of K. pinnata cultured in vitro. Of these, the induction of an organized hypertrophic growth at the vein ending on the proximal side of leaf disks is a significant morphogenetic effect. This polarized hypertrophy is considered an exclusive auxin-mediated response, as the effect is completely reversed by auxin efflux inhibitor 2,3,5-triiodobenzoic acid. With the magnitude of hypertrophic growth from individual disks taken as a manifestation of putative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…More and more researches indicated that the action mechanism of TDZ can be closely linked to the biosynthesis and transportation of IAA. Jaiswal and Sawhney (2008) observed an organized hypertrophic growth at the vein ending on the proximal side of K. pinnata leaf disks induced by TDZ, which is considered an exclusive auxin-mediated response. Further experiment proved that the effect is completely reversed by auxin efflux inhibitor, 2,3,5-triiodobenzoic acid (TIBA).…”
Section: Involvement Of Phytohormonesmentioning
confidence: 89%
“…More and more researches indicated that the action mechanism of TDZ can be closely linked to the biosynthesis and transportation of IAA. Jaiswal and Sawhney (2008) observed an organized hypertrophic growth at the vein ending on the proximal side of K. pinnata leaf disks induced by TDZ, which is considered an exclusive auxin-mediated response. Further experiment proved that the effect is completely reversed by auxin efflux inhibitor, 2,3,5-triiodobenzoic acid (TIBA).…”
Section: Involvement Of Phytohormonesmentioning
confidence: 89%
“…In addition, it exhibits clonal regeneration from roots and, more importantly, from detached leaves. New clonal plantlets are potentially formed from all undifferentiated meristem in the marginal notches of the crenated leaves (Jaiswal and Sawhney ).…”
Section: Methodsmentioning
confidence: 99%
“…Secondly, although kinetin is an adenine-type, synthetic, more stable cytokinin that persists in plants, it is also regulated by cytokinin oxidase (Nogue et al, 2003) and this could be a probable reason why media containing kinetin or ZR resulted in comparable numbers of cultivars with regeneration capacity (Yamada et al, 2001;Osugi and Sakakibara, 2015;Bhatla and Lal, 2018). Thirdly, TDZ is a synthetic phenyl-urea that inhibits the activity of cytokinin oxidase, probably due to its auxin-like properties and persistence in plants (Bilyeu et al, 2001;Nogue et al, 2003;Jaiswal and Sawhney, 2008). However, some cultivars produced RE > 10% on media containing TDZ, indicative of type on RE was evident, our data clearly demonstrated that genotype plays a more important role in RE than cytokinin type.…”
Section: Genotype and Cytokinin Dependentmentioning
confidence: 99%